ANALISIS PENGELOLAAN DANA BANTUAN LANGSUNG TUNAI-DANA DESA (BLT-DD) UNTUK MASYARAKAT DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG YANG TERDAMPAK PANDEMI COVID-19 - Anis Satul Fitriani; Nur Ida Iriani; Rizky Aprilia Dwi Susanti (Unitri Press, 2021)
This study aims to determine the management of Village Cash Direct Assistance (BLT-DD) funds in Landungsari Village, Dau District, Malang Regency which was affected by the Covid -19 pandemic. The type of research that has been used was descriptive qualitative using a case study approach obtained from primary data sources and secondary data sources. This study also uses data collection techniques through observation, interviews, documentation and literature study, then data analysis using interactive methods and validity testing using triangulation. The result showed that in the management of direct village cash assistance funds, it was in accordance with government regulations and laws as well as in the data collection flow which was very transparent and sele ctive in verifying data, so that in the distribution of village cash direct assistance funds (BLT-DD ) was able to run well even though the health protocols were still not implemented, while in reporting the realization of the program, it was reported by including photo evidence of documentation of the distribution of direct village cash assistance (BLT-DD).